Losing track of time through delayed body representations - Fritz, Thomas H.; Steixner, Agnes; Boettger, Joachim; Villringer, Arno (Frontiers in Psychology, 2015)
The ability to keep track of time is perceived as crucial in most human societies. However, to lose track of time may also serve an important social role, associated with recreational purpose. To this end a number of social technologies are employed, some of which may relate to a manipulation of time perception through a modulation of body representation. Here we investigated an influence of real-time or delayed videos of own-body representations on time perception in an experimental setup with virtual mirrors. Seventy participants were asked to either stay in the installation until they thought that a defined time (90 s) had passed, or they were encouraged to stay in the installation as long as they wanted and after exiting were asked to estimate the duration of their stay. Results show that a modulation of body representation by time-delayed representations of the mirror-video displays influenced time perception. Furthermore, these time-delayed conditions were associated with a greater sense of arousal and intoxication. We suggest that feeding in references to the immediate past into working memory could be the underlying mental mechanism mediating the observed modulation of time perception. We argue that such an influence on time perception would probably not only be achieved visually, but might also work with acoustic references to the immediate past (e.g., with music).